Is experiencing care as collaborative associated with enhanced outcomes in inpatient eating disorders treatment?. Issue 5 (3rd September 2021) - Geller, Josie; Maiolino, Nadia; Samson, Lindsay; Srikameswaran, Suja
ABSTRACT: In eating disorders inpatient care, mandatory treatment components are central to effective service delivery. Thus, fostering a collaborative care environment that supports autonomy, competence, and connection can be challenging. This study examined whether collaborative care is associated with better outcomes in adult inpatient treatment and explored a possible determinant of collaborative care, the manner in which mandatory treatment components were delivered (e.g. consistent implementation of weight gain guidelines, provision of choices regarding intensity of treatment). Inpatients (N = 146) completed measures of eating disorder symptoms, psychological functioning and readiness and motivation for change, pre and post-treatment. At post, they also completed measures of collaborative care, treatment satisfaction, and a new measure designed to evaluate patients' experiences of mandatory treatment components. After controlling for baseline symptom levels, multiple regression analyses determined that collaborative care was associated with improvements in nearly all symptom domains. Collaborative care was also associated with patient satisfaction and the manner in which mandatory treatment components were delivered (e.g. consistency, provision of choices). In sum, a collaborative environment was associated with improvements in motivation, eating disorder symptoms, and psychiatric functioning and one way in which this may be achieved is in the manner in which mandatory treatment components are delivered.